Джерела з вивчення розвитку електротехнічної галузі України другої половині ХХ ст. - Тверитникова, Олена Євгенівна (My University, 2016)
Проведено аналіз основних джерел, що містять інформацію стосовно розвитку електротехнічної галузі України другої половини ХХ ст. Масив джерел класифіковано за основними ознаками, виділено та описано групи. До джерельної бази залучено матеріли наукових досліджень фахівців-електротехніків, архівні документи, нормативно-правові акти, матеріали музеїв, наукові збірники, мемуари, матеріали інтерв’ю. Вивчення означених матеріалів дозволило встановити низку нових проблем з розвитку електротехнічної науки, що потребують окремого наукового дослідження.

The analysis of the main sources containing information about the development of the electrotechnical industry in Ukraine in the second half of the twentieth century is conducted. The source array is classified by relevant characteristics; the groups are identified and described. The source base includes materials of scientific researches made by specialists-electricians, archival documents, laws and regulations, museum materials, scientific collections, memoirs, interviews materials. The study of these materials allowed establishing a number of new problems for the development of electrotechnical science, requiring separate scientific researches.
The sources of the study of development of electrotechnical branch in Ukraine during the second half of the XX century
Keywords: науково-дослідна робота; вища технічна освіта; архівні матеріали; джерельна база; scientific research; higher technical education; archival materials; key base